Hybridisation as a Potential Extinction Threat to an Endangered Australian Frog - Gracie Liu; Jodi J. L. Rowley (Ecology and Evolution)
ABSTRACT Of the many threats to species' survival, genetic threats such as hybridisation and introgression are often overlooked. Threatened or range‐restricted species that hybridise with more abundant and widespread relatives can be particularly vulnerable to declines or extinction via demographic or genetic swamping. Conservation of these species requires detection of hybridisation, but this can be difficult when hybrids are morphologically indistinguishable from parental species (i.e., cryptic). We used single nucleotide polymorphism data to examine hybridisation and introgression between the endangered Booroolong frog (Litoria booroolongensis) and the more abundant eastern stony creek frog (Litoria wilcoxii), two Australian stream frog species not previously reported to hybridise. To assess whether hybrids and parental individuals could be identified by phenotype, we compared morphological and genotypic classifications of individuals. Genotyping revealed relatively high rates of hybridisation and introgression (19% (24/126) were F1 or F2 hybrids, or backcrosses) in the New South Wales Central Tablelands. Hybrids were present in all sites where the species were syntopic (five of seven sites), suggesting that hybridisation is constrained primarily by a lack of opportunity. Within these sites, the median rate of hybridisation was 31.8% (range: 5.3–100%). Based on the likely extent of syntopy, hybridisation is plausible across more than 70% of the geographic range of L. booroolongensis, with potentially negative consequences for the species' persistence. Concerningly, only 42% of hybrids were correctly identified by morphology. Our results emphasise the need for genetic data to accurately distinguish hybrids and suggest that hybridisation could be occurring undetected between many related species, representing a potentially insidious threat to threatened and range‐restricted species. Conservation policies will need to consider the possibility of hybridisation and evaluate its consequences to appropriately manage and prevent further declines of threatened species.